Aktivitas Antibakteri Ekstrak Etanol Porifera (Spongia Officinalis ) terhadap Staphylococcus Aureus ATCC 25923 - Indria Hafizah; Fine Farhani Muliati; Sulastrianah Sulastrianah (Halu Oleo University, 2016)
Staphylococcus aureus is the most dangerous of all of the many comman staphylococcal bacteria. It stains gram positive and is non moving small round shaped or non motile cocci..Porifera (Spongia officinalis) are lowly organised less evelved animals and can be used as the medication resources. The aim of this study was to inveftigate antibacterial extract etanol of Porifera (Spongia officinalis)against the growth of Staphylococcus aureus ATCC 25923.Present study was an experimental in vitro test. Antibacterial activity assays were carried out by the disc diffusion method. Antibacterial activity was determined by the clear zone formed around the papaer disc and minimum inhibitor concentration which could inhibit the growth of Staphylococcus aureus ATCC 25923.The results are supported by the presence of secondary metabolite by phytochemical test such as alkaloid, terpenoid, steroid, saponin and tanin.Extract ethanolof Spongia officinalis. Extract etanol Spongia officinalishas antibacterial activity againts Staphylococcus aureus ATCC 25923. Minimum inhibitory concentration from the ekstrak etanol Spongia officinalis was 10 ppm.Conclution ; Extract etanol Spongia officinalishas antibacterial activity againts Staphylococcus aureus ATCC 25923Keywords: Spongia officinalis, Staphylococcus aureus, Antibacterial activities, MIC (Minimal Inhibitory Consentration)